2021
DOI: 10.18331/sfs2021.7.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different stocking density on growth, survival on Litopenaeus vannamei (Boone, 1931) in summer and monsoon crop in province of Gujarat States in India

Abstract: A shrimp Pacific White shrimp, Litopenaeus vannamei growth performance study during summer (S) and monsoon (M) was taken up for 120 days. The stocking density was 30, 40, 50, 60, 70 and 80pc/m 2 in six different treatments with three replicate. Experiment was conducted in 18 commercial culture pond having 0.5 ha size. The initial average body weight of shrimp post larvae during summer and monsoon crop at stocking was 0.06±0.01g and 0.06±0.04g, respectively. The data revealed significant (p<0.05) difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Hence, the growth rate in this study was within a good range with the DGR between 0.08 and 0.42 g before the mortality event as shown in Table 1. After a mortality event, the DGR of shrimp increased which can be attributed to research conducted by Kotiya and Vadher (2021), which demonstrated that shrimp growth is inversely proportional to stocking density. Consequently, the significant reduction in stocking density led to an increase in the DGR of shrimp.…”
Section: Growth Analysismentioning
confidence: 99%
“…Hence, the growth rate in this study was within a good range with the DGR between 0.08 and 0.42 g before the mortality event as shown in Table 1. After a mortality event, the DGR of shrimp increased which can be attributed to research conducted by Kotiya and Vadher (2021), which demonstrated that shrimp growth is inversely proportional to stocking density. Consequently, the significant reduction in stocking density led to an increase in the DGR of shrimp.…”
Section: Growth Analysismentioning
confidence: 99%
“…In this farm economic section the various inputs cost contribution was calculated to produce one kg of shrimp in Amreli district and the details were furnished in ) will have higher survival%, low feed cost, high FCR, low fuel cost, total variable cost, low count (no of shrimp/kg), high price, higher net income and higher Net profit are all the parameters that shows that lower stocking density of shrimp ends with more net income compare with 40,50,60,70 and 80 (no of shrimp/m 2 ) of stocking density in pond [25].…”
Section: The Average Cost Analysis For the Cultured Shrimp Farming Un...mentioning
confidence: 99%